Elementy szkolenia w piłce nożnej. Różnice w szkoleniu klubu polskiego i niemieckiego = Training elements in football. Differences in the training system between polish club and german club - Kalinowski, Paweł; Judreczka, Katarzyna (Journal of Education, Health and Sport, 2015)
Kalinowski Paweł, Judreczka Katarzyna. Elementy szkolenia w piłce nożnej. Różnice w szkoleniu klubu polskiego i niemieckiego = Training elements in football. Differences in the training system between polish club and german club. Journal of Education, Health and Sport. 2015;5(11):542-550. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35696 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A542-550 http://pbn.nauka.gov.pl/works/684760 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Kalinowski Paweł, Judreczka Katarzyna. Elementy szkolenia w piłce nożnej. Różnice w szkoleniu klubu polskiego i niemieckiego. Quality in Sport. 2015;1(3):20-27. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%283%29%202015%2C%20s.%2020-27 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Paweł Kalinowski, Katarzyna Judreczka Zakład Teorii Sportu Akademia Wychowania Fizycznego w Poznaniu Elementy szkolenia w piłce nożnej. Różnice w szkoleniu klubu polskiego i niemieckiego Training elements in football. Differences in the training system between polish club and german club Streszczenie We współczesnej piłce nożnej, kontrola i monitorowanie treningu może zwiększyć efektywność nauczania jak również zapewnienie trenerom i sportowcom kompleksowych warunków treningowych. Uzyskiwane wyniki przez reprezentację Polski w piłce nożnej powodują chęć znalezienia przyczyny takich rezultatów. Celem artykułu jest próba pokazania różnic w treningu piłki nożnej pomiędzy polskim i niemieckim klubem. Przedmiotem obserwacji i analizy byli gracze reprezentujący kluby polskie i niemieckie. Metodą badawczą było użycie bezpośredniej obserwacji i analizy wyników zespołów młodzieżowych. Słowa kluczowe: piłka nożna, Niemcy, Polska, trening, sport. Abstract In modern football control and monitoring of training can increase the effectiveness of teaching. It’s going to provide coaches and athletes comprehensive training conditions. The results obtained by the athletes representing football in Poland tend to looking for reasons causing this state of affairs. The aim was to try to show the differences in training football between Polish and German club. The subject of observation and analysis were players representing Polish and German club. Footballers presented the highest levels of sports as evidenced by participation in the highest league in Poland and Germany. The research method was used direct observation and an analysis of the results of youth teams. Key words: football, German, Poland, training.